Number of Shareholders and Stock Prices: Evidence From Japan - Amihud, Yakov; Mendelson, Haim; Uno, Jun (Journal of Finance, 1999)
Merton (1987) proposes that an increase in a firm's investor base increases the firm's value. In Japan, companies can reduce their stock's minimum trading unit—the number of shares in a “round lot”—which facilitates trading in the stock by small investors. We find that a reduction in the minimum trading unit greatly increases a firm's base of individual investors and its stock liquidity, and is associated with a significant increase in the stock price. Further, the stock price appreciation is positively related to an increase in the number of shareholders.